The cortical processing of facial emotional expression is associated with social cognition skills and executive functioning: A preliminary study - Petroni, Agustín (2011)
Several lines of experimental evidence support an association between facial processing and social cognition, but no direct link between cortical markers of facial processing and complex cognitive processes has been reported until now. In the current study, we tested the hypothesis that cortical electrophysiological markers for the processing of facial emotion are associated with individual differences in executive and social cognition skills. We tested for correlations between the amplitude of event-related potentials (N170) in a dual valence task and participants' scores on three neuropsychological assessments (general neuropsychology, executive functioning, and social cognition). N170 was modulated by the stimulus type (face versus word) and the valence of faces (positive versus negative). The neural source of N170 was estimated to be the fusiform gyrus. Robust correlations were found between neuropsychological markers and measures of facial processing. Social cognition skills (as measured by three tests: the Reading the Mind in the Eyes test, the Faux Pas test, and the Iowa Gambling Task) correlated with cortical measures of emotional discrimination. Executive functioning ability also correlated with the cortical discrimination of complex emotional stimuli. Our findings suggest that the cortical processing of facial emotional expression is associated with social cognition skills. © 2011 Elsevier Ireland Ltd.